Pemberdayaan penyandang disabilitas melalui community development KSM batik percik - Shindi Yana Desi Rahma Sari; Rizza Megasari (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2021)
The existence of Persons with Disabilities with Diversity of Deafness and Mental Limitations is still often regarded as weak, helpless, unable to work and can even be said to be troublesome for others. With this assumption, a negative assessment emerges which causes some people with disabilities to feel inferior and lack self-confidence. When in fact they have skills that if developed will have a positive impact on them, for example to meet their needs. One of the efforts to improve the economic welfare of persons with disabilities is empowerment through community development of Batik Percik KSM. With this KSM, it will help people with disabilities to meet their daily needs. Persons with disabilities at this KSM will be given special training to create a product, namely batik percik. In the batik training, people with disabilities will be guided by the assistants at the Harapan Makmur KSM. Abstrak Keberadaan Penyandang Disabilitas dengan Ragam Tuna Rungu dan Keterbatasan mental ini masih sering dianggap sebagai kaum yang lemah, tidak berdaya, tidak bisa bekerja bahkan bisa hanya dikatakan menyusahkan orang lain. Dengan adanya anggapan tersebut muncul penilaian negatif yang mengakibatkan sebagian penyandang disabilitas ini merasa minder dan kurang percaya diri. Padahal sebenarnya mereka mempunyai keterampilan yang jika dikembangkan akan memberikan dampak yang positif bagi mereka misalnya untuk memenuhi kebutuhan hidupnya. Salah satu upaya untuk meningkatkan kesejahteraan ekonomi penyandang disabilitas ini adalah pemberdayaan melalui community development KSM batik percik. Dengan adanya KSM ini akan sedikit membantu penyandang disabilitas tersebut untuk memenuhi kebutuhan hidupnya. Penyandang disabilitas pada KSM ini akan diberikan pelatihan secara khusus untuk menciptakan sebuah produk yakni batik percik. Dalam pelatihan membatik penyandang disabilitas akan dibimbing oleh para pendamping di KSM Harapan Makmur tersebut.